Gamma Radiosynthesis of Colloidal Silver Nanoparticles Stabilized in ι-Carrageenan Under Atmospheric Gases: A Surface Plasmon Resonance Based Study - D. P. Perkasa; M. Y. Yunus; Y. Warastuti; B. Abbas (PPIKSN-BATAN, 2021)
ι-Carrageenan is a biodegradable and biocompatible biomaterial which potentially stabilizes colloidal silver nanoparticles (AgNPs). The present study explored gamma radiosynthesis of AgNPs at varied concentration of ι-carrageenan solutions. The reaction system contained 1.0 mM silver precursor from silver nitrate salt. Gamma irradiation was conducted at doses up to 20 kGy under simple condition, i.e., atmospheric gases and without addition of hydroxyl radical scavenger. The behavior of AgNPs in suspension was characterized based on their surface plasmon resonance (SPR) absorption spectra which were measured using UV-vis spectrophotometer. The results show that colloidal AgNPs were successfully radiosynthesized due to dual stabilizing/reducing activity of ι-carrageenan. The degradation product of ι-carrageenan shows antioxidant activities, which increase the reducing condition of the reaction system. TEM micrograph reveals that the nanoparticles are spheroid in shape and monodisperse with an average particle size of below 10 nm. The SPR spectra indicate that the highest AgNPs concentration is found for irradiation at a dose of 10 kGy and ι-carrageenan concentration of 1.0 % (w/v). However, instability of AgNPs occurred a day after radiosynthesis due to oxidative dissolution and agglomeration. Further works on pH adjustment and optimization on irradiation dose and ι-carrageenan concentration are critical to improve the stability of colloidal AgNPs.